MUSLIM EDUCATORS OF DAGESTAN AND THE “WOMEN’S ISSUE” (ON THE MATERIALS OF “JARIDAT DAGISTAN” NEWSPAPER, 1913-1918) - Navruzov, Amir Ramazanovic (History, Archeology and Ethnography of the Caucasus, 2022)
History of the Muslim enlightenment in the North Caucasus of the first third of the 20th century in Dagestan historiography is a poorly-studied subject: the works of the reformers-educators in Arabic and other oriental languages are practically not introduced or interpreted. In attempt to close the gap in modern literature, the author of the article analyzes the journalistic heritage of the Dagestan reformers-educators on the “women’s issue”, published in the newspaper “Jaridat Dagistan” (1913-1918). The analyzed sources allow to trace the evolution of views of the reformers themselves on the “women’s issue”, as well as the full picture of emancipation of the Dagestan women in pre-Soviet and early Soviet periods – from the oppressed, dependent position, deprived of basic rights in the family and society – to gaining equal rights with men, realizing the right to education, obtaining a profession, voting rights, etc. The Dagestan reformers-enlighteners accepted the Soviet power and worked on their concept of building a new Muslim society, in which a mother was put in the center. They were tolerant towards other confessions, and considered Sharia a self-sufficient basis for their development and further integration into the Russian and global space. On issues such as the training and education of women, recruitment to the civil service, the position of women in society and participation in public and political life, we see a departure from the traditional point of view of the reformers. Due to their active work, many issues of the emancipation of the Dagestan woman were resolved. However, many of them (for example, the issue of women’s Muslim education and upbringing, professional training, participation in public life, etc.) are quite relevant in current times.